Operational pattern and contribution of urban farming in an emerging megacity: evidence from Lagos, Nigeria - Lawal, Mohamed Olaitan; Aliu, Ibrahim Rotimi (Bulletin of Geography. Socio-economic Series, 2012)
Urban farming is rapidly growing in many cities in Nigeria including a leading African megacity Lagos, although urban stakeholders have paid little attention to the trend over time. The rate of growth of urban farming and its contributions to Lagos state's food supply strategy is worthy of note. In Lagos farming activities are practiced and performed by some able bodied migrants from all parts of the country, who for many reasons could hardly have been absolved by the aggressive urban economy of the city. A close watch on the practitioners reveals a pattern of operation which requires deeper inquiry. A total of 202 urban vegetable farmers were interviewed in four areas of Lagos state to provide primary data for this study. Results from the study showed that an average farmer owns a farm plot of below 120 m by 60 m usually linear and along the expressway, the green vegetable (Celosia argientes) alone constitutes about 97% of what is grown, beds are arranged in sizes of about 1.8 m long by 0.9 m wide and 0.3 m high with furrows in between. The farmers use the simplest local tools, chemical fertilizers, and strategically located irrigation wells. It was also found that the farmers use some part of the vegetables for household consumption, sell others to the local marketers, and contribute their own quota to stem the rising prices of vegetable produce in the local markets. It is therefore imperative on the stakeholders to re-examine the relevance of urban farming in the city and provide support for its growth.